2022
DOI: 10.1177/00033197211072598
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Meta-Analysis of Functional and Structural Markers of Subclinical Atherosclerosis in Women with Polycystic Ovary Syndrome

Abstract: The relationship between polycystic ovary syndrome (PCOS) and subclinical atherosclerosis remains unclear. We performed a comprehensive systematic review and meta-analysis to evaluate the effect of PCOS on functional and structural markers of subclinical atherosclerosis as measured by carotid intima-media thickness (cIMT), flow-mediated vasodilation (FMD), nitroglycerin-mediated vasodilation (NMD), pulse wave velocity (PWV), and coronary artery calcium (CAC). Standard mean differences (SMDs) or odds ratios (OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 127 publications
(77 reference statements)
1
2
0
Order By: Relevance
“…It should be noted that other studies found a lack of association [60,61]. A recent meta-analysis included 96 studies (5550 PCOS women) and revealed that PCOS contributes to subclinical atherosclerosis [62], thus confirming a previous study that noted the high heterogeneity among studies [63].…”
Section: Pcos and Atherosclerosissupporting
confidence: 69%
“…It should be noted that other studies found a lack of association [60,61]. A recent meta-analysis included 96 studies (5550 PCOS women) and revealed that PCOS contributes to subclinical atherosclerosis [62], thus confirming a previous study that noted the high heterogeneity among studies [63].…”
Section: Pcos and Atherosclerosissupporting
confidence: 69%
“…However, this risk does not consistently translate to an increased rate of cardiovascular events in the postmenopausal period. Studies have documented various preclinical changes in arterial structure among PCOS women of reproductive age [55]. A thorough systematic review and metaanalysis, encompassing 96 studies with 5550 PCOS patients and 5974 controls, sought to assess PCOS's impact on early indicators of atherosclerosis, using measurements like carotid intima-media thickness (cIMT), flow-mediated dilation (FMD), nitroglycerin-induced dilation (NMD), pulse wave velocity (PWV), and coronary artery calcium (CAC) [55].…”
Section: Cardiovascular Risk and Dyslipidemia In Pcosmentioning
confidence: 99%
“…Studies have documented various preclinical changes in arterial structure among PCOS women of reproductive age [55]. A thorough systematic review and metaanalysis, encompassing 96 studies with 5550 PCOS patients and 5974 controls, sought to assess PCOS's impact on early indicators of atherosclerosis, using measurements like carotid intima-media thickness (cIMT), flow-mediated dilation (FMD), nitroglycerin-induced dilation (NMD), pulse wave velocity (PWV), and coronary artery calcium (CAC) [55]. PCOS patients exhibited notably thicker cIMT, impaired FMD and NMD, increased PWV, and a higher rate of CAC compared to controls [55,56].…”
Section: Cardiovascular Risk and Dyslipidemia In Pcosmentioning
confidence: 99%